Motor origins of timbre in piano performance - Kaori Kuromiya; Yuya Kobayashi; Masato Hirano; Shinichi Furuya (Proceedings of the National Academy of Sciences, 2025)
Creativity in the arts, such as painting and musical performance, hinges on the ability to produce a wide spectrogram of perceptual experiences. In music, it has long been believed that the timbre of tones can be altered by nuanced movements of performers. Previous studies have described relationships between fundamental elements of auditory perceptions (e.g., loudness, tempo) and physical movements (e.g., force, speed), but it remains unknown whether and how delicate features of perceptual experiences such as tone timbre are manipulated through dexterous motor skills. Here, we bridge this gap using a twofold experimental approach. First, our listening test revealed that the timbral qualities pianists intended to express in piano playing were perceived as intended by both pianists and musically untrained individuals, with pianists showing a greater perceptual sensitivity to different timbres. Second, through a motor behavioral experiment using a noncontact, high-resolution sensing system, we identified five specific movement features in piano touch that were intricately linked to three categories of perceived timbre; weight, clarity, and brightness. Furthermore, the direct manipulation of a specific key movement feature resulted in systematic changes in perceived timbre, providing evidence for a causal relationship. The result indicates that pianists share common motor skills to modify perceived tone timbre by manipulating specific movement features. Our findings underscore the pivotal roles of subtle physical gestures in creating the rich timbral palette of piano tones, advancing our understanding of the intersection between motor control and artistic expression.